2020
DOI: 10.2106/jbjs.oa.20.00007
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Increasing Diversity in Orthopaedics

Abstract: Background: There are little data to explain why the surgical subspecialty of orthopaedic surgery struggles with improving the racial/ethnic composition of its workforce. The current work sought to determine what orthopaedic residency program directors and coordinators believe are the barriers to improving diversity at their own programs. Methods: Between November 17, 2018, and April 1, 2019, a 17-question survey was electronically distributed to the program directors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 25 publications
1
84
1
Order By: Relevance
“…Additionally, there was no significant improvement in racial/ethnic diversity among orthopedic residency programs over the same time period [107 • ]. A recent study similarly showed that Latino, African American, and Native American groups were significantly underrepresented in orthopedic residencies [108]. A more representative workforce from surgeon to physical therapists to athletic trainers may have a positive impact on disparities and treatment outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, there was no significant improvement in racial/ethnic diversity among orthopedic residency programs over the same time period [107 • ]. A recent study similarly showed that Latino, African American, and Native American groups were significantly underrepresented in orthopedic residencies [108]. A more representative workforce from surgeon to physical therapists to athletic trainers may have a positive impact on disparities and treatment outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, with orthopaedic surgery often cited being one of the least racially and sex diverse specialties in medicine, additional insight is needed concerning the influence of the pandemic on the diversity of applicants who applied, interviewed, and matched at orthopaedic residency programs. 24 - 26 …”
Section: Discussionmentioning
confidence: 99%
“…Survey-based demographic studies are often complicated by nonresponse and volunteer bias, which may skew results and produce incomplete data. 1 , 4 , 23 , 24 , 50 This study attempts to capture the entirety of HTP and head ATC perceived diversity, which may not be possible with survey techniques given the pitfalls mentioned above. Studies detailing associations among orthopaedic institutions’ faculty diversity, resident diversity, and the diversity of the applicant pool of medical students suggest the perception of diversity is an important factor.…”
Section: Discussionmentioning
confidence: 99%